IMPLEMENTASI PROGRAM BIMBINGAN DAN KONSELING BERBASIS ASSESMENT KEBUTUHAN DI PANTI ASUHAN TORIQUL JANNAH KOTA SERANG - Sabrina, Sabrina; Prabowo, Arga satrio; Nurmala, Meila Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of a needs assessment-based Guidance and Counseling Program is an effort to provide services that are appropriate to the problems and developmental needs of students. This activity aims to implement a Guidance and Counseling Program in the field of Physical Education and Health (JDK) based on the results of the needs assessment of elementary school-aged children at the Toriqul Jannah Orphanage, Serang City. The needs assessment was conducted using the General Problem Disclosure Tool (AUM) Format 1 SD as the basis for program development. Program implementation is carried out through classic guidance services, group guidance, group counseling, and individual counseling. Service materials include a healthy lifestyle, good sleep quality, positive daily activities, maintaining personal hygiene and health, and self- and time management. Evaluation is carried out through process evaluation and outcome evaluation to determine service implementation and achievement of program objectives. The implementation results indicate that all services can be implemented in accordance with the Service Implementation Plan (RPL) and service objectives are generally achieved. Participants showed increased understanding and awareness in implementing healthy lifestyle behaviors, maintaining personal hygiene, managing rest time, and managing daily activities. The evaluation results were mostly in the Good category, with some services improving from Sufficient to Good. Thus, the implementation of the Guidance and Counseling Program based on needs assessment has had a positive impact on the development of participants' understanding and awareness of physical and health problems, and can be used as a reference for the implementation of sustainable guidance and counseling services in orphanages.